Pediatrics - Osborn, Lucy M; Dewitt, Thomas G; First, Lewis R (Elsevier Mosby, 2005)
Extensively illustrated and uncommonly user-friendly, this brand-new text provides a logical, \"hands on\" approach to the care of the pediatric patient. Written by an international team of subspecialists and edited by an outstanding team of pediatric generalists, it offers expert coverage that can be applied in everyday practice-in a highly templated format that makes finding information a snap. Readers will find comprehensive coverage of basic science, health promotion and disease prevention, general and chronic medical care, newborn and adolescent care, mental health care, diagnostic and therapeutic interventions, and more. And, a bonus CD-ROM offers additional images, video clips, and other supplemental materials.Emphasizes clinical practice, including diagnosis, management, and referral.Offers authoritative guidance in a user-friendly, easy-access format.Organizes material according to the way pediatricians learn and practice-addressing the fundamentals of basic science and then health promotion and disease prevention.Features a \"mini-index\" at the end of each chapter to assist the reader in finding information quickly and easily.Includes a wealth of tables and charts, as well as clinical photographs to aid in diagnosis, and algorithms for guidance on treatment.Allows for quick access to important information with cross-referencing between chapters and the use of color-coded tabs.Comes with a bonus CD-ROM that includes additional images, video clips, and other supplemental materials.
Keywords: pediatrie; Pediatrics